Novel Compound Heterozygous Mutations in Two Families With Bernard–Soulier Syndrome - Minkov, Milen; Zeitlhofer, Petra; Zoubek, Andreas; Kager, Leo; Panzer, Simon; Haas, Oskar A. (Frontiers in Pediatrics, 2021)
Background: Bernard–Soulier Syndrome (BSS) is a rare autosomal recessive bleeding disorder with large platelets and thrombocytopenia. It is caused by homozygous or compound heterozygous mutations in the GP1BA, GP1BB, or GP9 genes, which together encode the platelet surface receptor glycoprotein complex GPIb-IX-V. Objectives: We report two novel heterozygous mutations in the GP1BA and the GP9 genes, respectively. Patients/Methods: We analyzed the platelet glycoprotein expression by flow cytometry and screened the relevant genes for responsible mutations in two unrelated families. Results: Flow cytometric analyses revealed the absence of CD42a (GPIX) and CD42b (GPIb) on the platelets in the two affected siblings of family 1 and a significantly reduced expression of CD42b (GPIb) in the patient of family 2. In the two siblings, we identified a known frameshift (c.1601_1602delAT) and a novel nonsense mutation (c.1036C>T) in the GP1BA gene that abrogated the production of GP1bα. In the other patient, we found a novel missense mutation (c.112T>C) that was co-inherited with a common one (c.182A>G) in the GP9 gene, respectively. All analyzed heterozygous carriers were asymptomatic and had a normal GPIb-IX-V expression. Conclusions: The two novel GP1BA and GP9 mutations reported herein increment the number of causative genetic defects in BSS.